Impacts of climate change-induced natural hazards on women and their human rights implications: A study in the southwest coast of Bangladesh - Md Shamsuddoha; Md. Akib Jabed; Md Shahnul Islam; Naznin Sultana; Al Imran; Sheikh Nur Ataya Rabbi; Tanje Un Jenat; Shanjia Shams; Mir Mehoraf Sharif (Elsevier, 2024)
Women in coastal areas are particularly vulnerable to climate change impacts due to existing gender inequality and socio-cultural norms in Bangladesh. This research aims to explore the vulnerability of women to climate change-induced natural hazards, the challenges they face due to the chain impacts of climate change, and the resulting violation of women's rights. Quantitative and qualitative data were used in this study, where 260 structured questionnaire surveys and 15 Focus Group Discussions were performed at Mongla and Shyamnagar Upazilas in Bagerhat and Satkhira districts, respectively. The quantitative data were analyzed using SPSS 26.0 software, and qualitative data was analyzed thematically. The results disclose that most respondents in Mongla and Shyamnagar reported an increase in the occurrence rate of climate change-induced natural hazards, with cyclones, salinity, and riverbank erosion being the most devastating in Mongla and cyclones, salinity, and storm surges in Shyamnagar. It affects the lives and livelihoods of people, with women being particularly vulnerable due to limited access to education, healthcare, and economic opportunities, and women's rights are violated in these areas. Half of the study area's population has been suffering from infections or inflammation in reproductive organs, especially among fisherwomen. The findings of this study recommend that provisions for alternative livelihoods should be made for women, and all women must be brought under the umbrella of fair social safety net programs.